EVALUASI ADOPSI TEKNOLOGI BUDIDAYA DAN KELAYAKAN USAHATANI PADI DI PROVINSI SULAWESI SELATAN - Amar K Zakaria (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
Rice  is the strategic commodity as the main foodstuff and the source of the income of most rural households. The application of cultivation technology played an important role towards the increase in the production and the productivity of  lowland rice. Therefore, the application of the innovation of recommendation technology in the level of the farmer was the strategy in the increase program in the production of the national  rice  towards  the  continuous  self-sufficiency. This  research  was  carried  out during 2012 in the Sidrap Regency and Luwu, Provinsi South Sulawesi with the survey method. The primary data was gathered through the interview to the respondent's 80 farmers  with  the  questionnaire  structure  filling. The  data  was  processed  with  cross tabulation  and  the  level  of  the  appropriateness  of  the  farming  was  measured  with Gross B/C the ratio and  profitability. Results of the research showed that adoption of rice technology in the farmer level was adopted with technology recommendation. The analysis of benefit and cost to get gross B/C > 1, based on that the farming of lowland rice in the research territory gave the profit and economically appropriate was made an effort operation.